2018
DOI: 10.1016/j.celrep.2018.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Functional CD169 on Macrophages Mediates Interaction with Dendritic Cells for CD8+ T Cell Cross-Priming

Abstract: Splenic CD169 macrophages are located in the marginal zone to efficiently capture blood-borne pathogens. Here, we investigate the requirements for the induction of CD8 T cell responses by antigens (Ags) bound by CD169 macrophages. Upon Ag targeting to CD169 macrophages, we show that BATF3-dependent CD8α dendritic cells (DCs) are crucial for DNGR-1-mediated cross-priming of CD8 T cell responses. In addition, we demonstrate that CD169, a sialic acid binding lectin involved in cell-cell contact, preferentially bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 58 publications
13
106
0
Order By: Relevance
“…Interestingly, Siglec-1 + macrophages from the spleen marginal zone have been shown in the vesicular stomatitis virus (VSV) mouse model to support a locally restricted enforced viral replication by down-modulating type I IFN responsiveness thus providing a source of viral antigen required to elicit a protective immune response (46). Moreover, Siglec-1 + macrophages can transfer viral antigens to cDC1s which in turn cross-prime CD8 + T cell responses (47). Importantly, this antigen transfer was mediated by Siglec-1 on the macrophages interacting with sialylated proteins present on cDC1 cell surface (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Siglec-1 + macrophages from the spleen marginal zone have been shown in the vesicular stomatitis virus (VSV) mouse model to support a locally restricted enforced viral replication by down-modulating type I IFN responsiveness thus providing a source of viral antigen required to elicit a protective immune response (46). Moreover, Siglec-1 + macrophages can transfer viral antigens to cDC1s which in turn cross-prime CD8 + T cell responses (47). Importantly, this antigen transfer was mediated by Siglec-1 on the macrophages interacting with sialylated proteins present on cDC1 cell surface (47).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Siglec-1 + macrophages can transfer viral antigens to cDC1s which in turn cross-prime CD8 + T cell responses (47). Importantly, this antigen transfer was mediated by Siglec-1 on the macrophages interacting with sialylated proteins present on cDC1 cell surface (47). Thus, Siglec-1 expression may also confer blood pre-DCs the capacity to recruit and instruct the help of crosspresenting cDC1s.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 These macrophages present viral antigens to activate specific T cells, to induce activation, clonal proliferation, and subsequent killing of infected target cells through secretion of perforin, granzyme B, and interferon-γ etc. [10][11][12] Moreover, these activated T cells also egress from spleen and LNs into blood circulation and play immune surveillance roles. 13 Unfortunately, our previous work has shown that lymphocytopenia is prevalent in COVID-19 patients, especially in aged and critically ill cases, suggesting that the immune system from COVID-19 patients might be neutralized by infection.…”
Section: Introductionmentioning
confidence: 99%
“…The spleen has long been known as the main filter for blood and its microanatomic structure is optimized for intercepting circulating blood-borne pathogens. Splenic CD169+ macrophages, a subset of macrophages located in the splenic marginal zone, are on the front line of host defense to encounter blood borne pathogens (9)(10)(11). In addition to its defensive role, the human spleen also stores approximately one-third of the platelets that are generated by the bone marrow (12) and through retention of infused platelets the spleen can also affect platelet transfusion outcome (13).…”
Section: Introductionmentioning
confidence: 99%